Pengaruh Senam Ergonomik Terhadap Penurunan Tekanan Darah Di Dusun I Desa Tanjung Anom Kecamatan Pancur Batu Tahun 2022 - Elpriska Elpriska (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2022)
This study aims to evaluate the impact of ergonomic training on blood pressure in hypertension sufferers in Hamlet I, Tanjung Anom Village, Pancur Batu District. The research method used One Group Pre-test – Post with purposive sampling technique and 10 respondents from a population of 50 met the criteria. Data was collected through ordinal scales and observation instruments. The results of the Wilcoxon Signed Ranks Test analysis with SPSS showed a significance of <0.05 (p=0.00), indicating the influence of ergonomic exercise on reducing blood pressure. The conclusion of this study states that ergonomic exercises are effective in reducing blood pressure in hypertension sufferers in Hamlet I, Tanjung Anom Village, Pancur Batu District in 2022.